INDONESIA LAW REPORT (ILR) AS A PLATFORM FOR PUBLISHING SUPREME COURT JURISPRUDENCE: A LITERATURE REVIEW OF ITS ROLE IN COLLECTING, SELECTING, AND PUBLISHING NEW LEGAL FINDINGS RELEVANT TO THE NEEDS OF TODAY'S SOCIETY - Sendi Sanjaya SH; Gunawan Widjaja (Adisam Publisher, 2025)
The Indonesia Law Report (ILR) is the Supreme Court's official platform that functions as a medium for collecting, selecting, and publishing jurisprudential decisions that contain new and important legal discoveries. This study uses a literature review method to examine the role of the ILR in developing a systematic storage of jurisprudence, gathering strategic decisions, and disseminating legal information relevant to the needs of today's society. The results of the study show that ILR contributes greatly to improving accessibility, transparency, and legal education for legal practitioners, academics, and the general public. With regular publications and digital presentation, ILR facilitates the adjustment of law to social dynamics and technological developments in an effective and responsive manner. The existence of ILR strengthens the quality and accountability of the judicial process and supports sustainable legal reform in Indonesia.